Evaluation of healthcare providers’ approach towards pandemic influenza and their vaccination ratio - Asan, Ali; Kose, Sukran; Sacar, Suzan; Polat, Yusuf; Ugurcan, Dogac; Catak, Binali; Turgut, Huseyin (The European Research Journal, 2015)
Objectives. Pandemic influenza is a contagious disease caused by the new pandemic influenza A H1N1 virus, originated from the genetic combination of human, pig and avian influenza viruses. Our research aimed to determine the level of pandemic influenza vaccination in healthcare providers and the factors influencing this level. Methods. Doctors, midwives and nurses working in primary, secondary and tertiary health institutions in Denizli established the universe of the research. Four nurses visited these health institutions on five workdays between the 4th and 8th of April 2011, informed the healthcare providers that participation to the research was voluntary and handed over data collection forms in the institutions visited. Then, these data collection forms were collected by the same nurses. Research data were analyzed with SPSS package program. Frequency, percentage, chi-square and logistic regression analyses were used in the evaluation. Results. 44.7% of the healthcare providers participating in the study stated that they had been vaccinated with pandemic influenza vaccine. When factors effecting the vaccination decision with pandemic influenza vaccine of the individuals participating the study was evaluated; statistically significant difference between vaccination and occupation (p=0.001), sex (p=0.001), and age (p=0.026) was detected. The proportion of doctors, males and individuals older than 40 years was higher among the vaccinated professionals. Conclusions. It is important to make announcements about vaccination with determination and by taking support from media and non-governmental organizations. Statements and explanations should be released with this in mind and media, and nongovernmental organizations should also take responsibility regarding this matter.